PSYCHOLOGICAL CHARACTERISTICS OF MILITARY LEADERSHIP - Abamara, Nnaemeka C (Practicum Psychologia, 2018)
This paper explores positive psychological characteristics of military leadership. The military in this paper is used to embrace all the armed forces of a country. In Nigeria, the armed forces include the army, the Air force and the Navy. As a very formal organization rules and order are strict and roles are not discretionary. Certain characteristics have been posited as germane for effective leadership in the military; firm and disciplined behaviour, ability to take decision and influence subordinates to key into same. Ability to enforce Conformity and obedience to the military authority and to punish defaulters also constitute very important role. The Big five personality model was used to evaluate the personality of military leaders, among the five models; openness to experience was posited by the author as requisite for military operations and duties. These characteristics in line with military ethos are cardinal to fostering and facilitating military efficiency.